Do Workers Benefit from Resource Booms in Their Home State? Evidence from the Fracking Era - John V. Winters; Zhengyu Cai; Karen Maguire; Shruti Sengupta (Global Labor Organization (GLO), 2019)
Fracking innovations revolutionized the United States oil and gas industry and facilitated a boom in energy production in states with oil and gas resources. This paper examines effects of oil and gas booms within a state on individual employment and earnings. To account for endogenous migration decisions, we instrument for oil and gas production in workers' state of residence via the predicted percent of oil and gas employment in their state of birth. We find statistically significant and economically meaningful positive effects. The bulk of the effects accrue to workers employed outside the oil and gas industry indicating sizable spillovers.
Keywords: J20; J30; Q40; R10; 330; Resource boom; Regional economic development; Employment; Wages; Income